Comparative Effectiveness of Antidepressant Medication versus Psychological Intervention on Depression Symptoms in Women with Infertility and Sexual Dysfunction - Hajar Pasha; Zahra Basirat; Mahbobeh Faramarzi; Farzan Kheirkhah (International Journal of Fertility and Sterility, 2018)
Background Fertility loss is considered as a challenging experience. This study was conducted to compare the effectiveness of antidepressant medication and psychological intervention on depression symptoms in women with infertility and sexual dysfunctions (SD). Materials and Methods This randomized, controlled clinical trial study was completed from December 2014 to June 2015 in Babol, Iran. Of the 485 participants, 93 were randomly assigned in a 1:1:1 ratio to psychosexual therapy (PST), bupropion extended-release (BUP ER) at a dose of 150 mg/d, and control (no intervention) groups. The Beck Depression Inventory (BDI) was completed at the beginning and end of the study. Duration of study was eight weeks. Statistical analyses were performed by using paired-test and analysis of covariance. Results The mean depression score on the BDI was 22.35 ± 8.70 in all participants. Mean BDI score decreased significantly in both treatment groups (PST: P < 0.0001, BUP: P < 0.002) from baseline to end of the study, whereas intra-individual changes in BDI score were not significant in the control group. The decrease in mean BDI score was greater with PST compared to BUP treatment (P < 0.005) and the control group (P < 0.0001). The PST group showed greater improvement in depression levels (severe to moderate, moderate to mild) in comparison with the two other groups (P < 0.001). Drug treatment was well tolerated by the participants in the BUP group. Conclusion PST can be a reliable alternative to BUP ER for relieving depression symptoms in an Iranian population of women with infertility and SD (Registration number: IRCT2015042721955N2).